A copper-catalyzed approach for the synthesis of asymmetrical disubstituted 1, 2, 4-thiadiazoles via elemental sulfur-mediated decarboxylative redox cyclization. (16th February 2021) - Liu, Yafei; Zhang, Yurong; Zhang, Jun; Hu, Liang; Han, Shiqing
Graphical abstract: Highlights: The synthetic method of asymmetrical disubstituted 1, 2, 4-thiadiazoles mediated by element sulfur. Copper is as a catalyst in this method. The yield was moderate to good. Abstract: The variety of asymmetrical disubstituted 1, 2, 4-thiadiazoles are smoothly prepared by copper-catalyzed approach, which employed arylacetic acids and amidines as substrates, and elemental sulfur to mediate decarboxylative redox cyclization. The advantages of this method are simple, efficient, and ligand-free. In addition, this method can provide products in moderate to good yields.